The unforeseen future by strategy gurus : the interplay between sense making, sense giving, and the role of language - Dias, Chamudi (2023)
Strategy gurus play a crucial role in the field of strategy due to their knowledge and contributions to the development and execution of strategy. In the preceding decades, debates have been sparked on guru identities, particularly in terms of interpreting un-foreseeable future events. Gurus demonstrate their prognostic abilities, through the use of narratives and an emphasis on numerous phenomena and concepts, compared to novices. In contrast, sense-making research is currently conducted in all disciplines, particularly to comprehend how human thoughts, behaviors, and actions operate and interact with one another. However, research in the field of sense-making and guru event predictions is viewed as a potential future area of study, particularly in terms of the role that communication and language play in the process.